2017
DOI: 10.22159/ajpcr.2017.v10i3.16435
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids as Source of Anti-Inflammatory Compounds

Abstract: Terpenoids accounts for the major class of secondary metabolites produced by plants. It shows defense activity against environmental stress and help to heal injuries. Medicinal plants are rich in monoterpenoids, diterpenoids, sesquiterpenes, triterpenes, tetraterpenes, and ceramide. A number of therapeutic applications such as antibacterial, antimicrobial, antitumor, anti-inflammatory activity have been identified. Terpenoids are compounds similar to terpenes derived from 5-carbon monomer isoprene units. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 36 publications
0
45
0
4
Order By: Relevance
“…It helps to cope up stress condition and supports defense activities. Plants with medicinal properties are rich in these compounds such as ceramide and different forms of terpenoids [35]. Pentacyclic triterpenoid and saponins are collectively known as centelloids.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…It helps to cope up stress condition and supports defense activities. Plants with medicinal properties are rich in these compounds such as ceramide and different forms of terpenoids [35]. Pentacyclic triterpenoid and saponins are collectively known as centelloids.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Phytochemical properties of the samples had a correlation with their therapeutic properties. Some studies have reported that alkaloid and terpenoids compounds have many potentials as antibacterial [2,3], anticancer and antitumor [4], antidiabetic and antioxidant [5], and anti-inflammatory [6,7] agents. Moreover, alkaloids from marine invertebrates such as sponges are reported to be anti-inflammatory potentials [21].…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…This study investigated a new source from nature, namely sponges, as a potential alternative medicine that can reduce inflammation. There are some active compounds from sponges that have proven beneficial to humans such as anti-bacteria, anticancer, antidiabetic and antioxidant, antifouling, and anti-inflammatory [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide 2-3 % of population suffering from such kind of skin disease [1]. The exact cause of this disease is still not clear but it is assumed that it may be mainly due to the activation and migration of T cells to the dermis which triggering the release of cytokines tumor necrosis factor alpha (TNF-α) ultimately lead to the inflammatory process and the rapid proliferation of skin cells.…”
Section: Introductionmentioning
confidence: 99%